The Rumen Metabolism Product in Male Sheep - Suwandyastuti, SNO (ANIMAL PRODUCTION, 2007)
Generally, sheep are capable to cosume the forage about 90 percent of their dry matter requirement.  In Indonesia, sheep generally accumulated in low land area, so that the requirement to be supply by dried field grass only. An experiment have been conducted at the Experimental Farm, Faculty of Animal Science, General Soedirman University.  Twenty seven male sheep were used in a Completely Randomized Blok Design of three replication.  The factors tested were : three levels of dried field grass at: 0, 21.25 and 42.50 percent dry matter of ration.  The variables measured were: (1) crude fibre digestion coefficient; (2) Rumen metabolism product: volatile fatty acids, espencially acetate (C2), propionate (C3), butyrate (C4), and valerate (C5). The digestion trial was carried out by the Total Collection methods and the production of individual volatile fatty acids were determined by chromatography technique.  The analysis of covariance shown, that there was no significantly effects of treatment tested upon the crude fibre digestion coefficient (P>0.005), but there were a highly significant effect ( P<0.001) upon the production of acetate ((C2) and propionate (C3).  The relationship of ceude fibre digestion coefficient with all of the rumen metabilism product were shown to be same, in cubic form.  Based on the crude fibre digestion coefficient and the production of individual volatile fatty acid, it was found that dried fields grass can be used up to 42.50 percent of ration dry matter for male sheep. (Animal Production 9(1): 9-13 (2007) Key Words : metabolism, forage, grass, sheep